THE EFFECTS OF CLUSTERING NEW WORDS IN SEMANTIC, THEMATIC OR UNRELATED SETS IN TEACHING VOCABULARY TO EFL LEARNERS - Sarıoğlu, Mustafa; Yıldırım, Özgür (My University, 2018)
Whether new vocabulary items should be taught in semantic, thematic or unrelated sets is a controversial issue in L2 lexical research. Although many studies suggest that presenting L2 words simultaneously in semantic sets has an interfering effect on the acquisition of those words, most of them have been conducted under strictly-controlled experimental conditions. Therefore, there is still a lack of classroom-based studies on this matter. With this in mind, this study aims to compare the effects of teaching new words in semantic, thematic and unrelated sets on EFL learners’ acquisition of these words in a natural classroom setting. 18 participants were taught the real L2 target words in one of these three types of clustering through pictorial flashcards. They were also provided with a number of meaningful encounters with the target words in sentential contexts. The results showed that all of these three clustering types supplied EFL learners with very efficient recognition and production of the target vocabulary not only immediately after the treatment but also three weeks later. The study findings did not reveal any interfering effect of presenting and practicing semantically related words at the same time in real classroom conditions.

Yabancı dil eğitiminde kelime öğretirken kelimelerin anlamsal, tematik ya da bağlantısız gruplar hâlinde öğretilmesi konusu hâlen tartışılmakta olan bir konudur. Öğretilecek kelimelerin aynı anda anlamsal olarak gruplandırılarak öğretilmesinin etkili olacağını öne süren pek çok çalışma olmasına rağmen bu çalışmalar genelde değişkenlerin kontrol altında tutulduğu deneysel çalışmalardır. Bu sebeple, sınıf içindeki doğal öğrenci davranışlarına odaklanan çalışmalara ihtiyaç duyulmaktadır. Bu çalışma da kelime öğretiminde kelimelerin anlamsal, tematik ya da bağlantısız gruplar hâlinde gruplanmasının öğrenme üzerindeki etkilerini doğal sınıf ortamında araştırmaktadır. Çalışmaya katılan 18 öğrenciye gerçek İngilizce kelimeler üç gruplama yönteminden biri kullanılarak öğretilmiştir. Çalışmanın sonuçları bütün gruplandırma yöntemlerinin kelime öğretimine katkısı olduğunu ortaya çıkarmıştır, fakat üç gruplandırma yönteminden herhangi birisinin diğerlerine göre daha etkili olduğu yönünde herhangi bir sonuca ulaşılamamıştır.
YABANCI DİL EĞİTİMİNDE KELİMELERİN ANLAMSAL, TEMATİK VEYA BAĞLANTISIZ HÂLDE GRUPLANDIRILMASININ ÖĞRENMEYE OLAN ETKİSİ
Keywords: Eğitim, Eğitim Araştırmaları